Strategi Perencanaan Sumber Daya Manusia Yang Efektif Untuk Meningkatkan Keunggulan Kompetitif (Studi Kasus Pada Kantor Desa Bengkak, Banyuwangi) - Nisa, Khoirotun; Khalikussabir, Khalikussabir; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the human resource (HR) planning strategies implemented at the Bengkak Village Office, Banyuwangi Regency, to enhance competitive advantage. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The research results show that HR planning is carried out through procurement, development, and evaluation based on the real needs of the village. The main strengths lie in the support of the village head, communication among staff, and openness to training. Weaknesses lie in budget constraints and unequal competencies. The strategies adopted have been adjusted to external environmental opportunities and threats. In conclusion, strategic HR planning plays an important role in driving excellent and competitive public services. Keywords: HR Planning, Strategy, Competitive Advantage, Village Government.